(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research paper examines environmentally friendly banking in India, with a particular emphasis on the tactics used by banks to promote sustainable growth. Its goal is to examine the many steps Indian banks have made to reduce environmental hazards and advance sustainable banking practices. The paper also examined the implementation obstacles that bank face and the possible advantage for the environment and the institution themselves. Research is based on secondary data. Research emphasisto improve sustainability, it is imperative that we promote awareness of, adopt, and practice green banking as much as we can in the cutting-edge corporate world of today.